Daughter of the Empire - Feist, Raymond E and Wurts, Janny (London Grafton, 1988)
In the world of Kelewan, Mara, Ruling Lady of the Acoma, struggles for survival against her rivals. Mara trades her heart for power as she marries the son of an enemy, while plotting his death.